Introduction to state-of-the-art multidimensional time-resolved spectroscopy methods - Kraack, Jan Philip; Buckup, Tiago (Topics in current chemistry, 2018)
The field of multidimensional laser spectroscopy comprises a variety of highly developed state-of-the-art methods, which exhibit broad prospects for applications in several areas of natural, material, and even medical sciences. This collection summarizes the main achievements from this area and gives basic introductory insight into what is currently possible with such methods. In the present introductory contribution, we briefly outline the general concept behind multidimensional laser spectroscopy, for instance by highlighting the often-employed analogy between multidimensional laser spectroscopy and NMR methods. Our initial introduction is followed by an overview of the most important and widely used multidimensional spectroscopies’ classification. Special emphasis is placed on how the contributing spectral region defines a natural way of grouping the techniques in terms of their information content. On this basis, we introduce the most important graphical ways in which multidimensional data is generally visualized.
Gesehen am 03.02.2018